Parameters consideration in designing a magnetorheological damper - Yazid, I. M. (2013)
This paper presents a simulation study of electromagnetic circuit design for a mixed mode Magnetorheological (MR) damper. The magnetic field generated by electromagnetic circuit of the MR damper was simulated using Finite Element Method Magnetics (FEMM) software package. All aspects of geometry parameters were considered and adjusted efficiently in order to obtain the best MR damper performance. Eventually, six different parameters approach were proposed; the selection of materials, the polarity of coils, the diameter of piston, piston rod and core, the shear and squeeze gaps clearance, the piston pole length and the thickness of housing.